"Aufräumungsarbeiten im Klassenkrieg. Nach den Kämpfen in Eisleben". Aus einem Kalender der KPD für 1926
"Aufräumungsarbeiten im Klassenkrieg. Nach den Kämpfen in Eisleben". Aus einem Kalender der KPD für 1926.